Kant and the Discipline of Reason. (23rd December 2013) - Chance, Brian A.
Abstract Kant's notion of 'discipline' has received considerable attention from scholars of his philosophy of education, but its role in his theoretical philosophy has been largely ignored. This omission is surprising since his discussion of discipline in the first Critique is not only more extensive and expansive in scope than his other discussions but also predates them. The goal of this essay is to provide a comprehensive reading of the Discipline that emphasizes its systematic importance in the first Critique. I argue that its goal is to establish a set of rules for the use of pure reason that, if followed, will mitigate and perhaps even eliminate our tendency to make judgments about supersensible objects. Since Kant's justification for these rules relies crucially on claims he has defended in the Doctrine of Elements, I argue further that, far from being a dispensable part of the Critique as commentators have tended to claim, the Discipline is, in fact, the culmination of Kant's critique of metaphysics.